Patients with Diabetes Mellitus without Complications at The Public Health Center Putri Ayu Jambi City (STIKES Telogorejo Semarang, 2022)
Diabetes mellitus isa set of metabolic disorders characterized by increased blood glucose levels (hyperglycemia) due to damage to the insulin system, insulin action, or both. Diabetes mellitus will accompany patients for life so that it will affect the anxiety of patients both from the state of physical, psychological, social and environmental health. This is a qualitative research by using phenomenological approach. This study aimed to determine the experience of psychological adaptation to patients with diabetes mellitus at the public health center Putri Ayu. This study used in-depth interview. Taking participants in this study as many as 5 people and 5 informants, it used purposive sampling technique, interview, observation and document review toward patients with diabetes mellitus. This study uses colaizi data analysis. The finding answer obtained 3 themes, namely: theme I response to loss of people with diabetes mellitus, theme 2 family support for people with diabetes mellitus, theme 3 coping strategies used by people with diabetes mellitus. The loss response indicated when diagnosed with diabetes mellitus is in the form of an acceptance and (acceptance) response (denial). Family support obtained by people with diabetes mellitus in the form of emotional support and information. Coping strategies used by people with diabetes mellitus are problem focused coping and emotional focused coping. For other researchers to conduct and continue qualitative research on the physiological adaptation experience of people with diabetes mellitus.